An extract of Leontopodium alpinum inhibits catagen development ex vivo and increases hair density in vivo. (6th June 2022) - Campiche, Remo; Le Riche, Alizée; Edelkamp, Janin; Botello, Alfonso Fernandez; Martin, Emmanuel; Gempeler, Mathias; Bertolini, Marta
Abstract: Objectives: Hair loss and reduction in hair volume are hallmarks of hair disorders, such as telogen effluvium, or male or female pattern hair loss, and hair ageing, which can cause severe distress in both men and women. Common anti‐hair loss drugs carry some side effects; therefore, novel, safer approaches targeting milder phenotypes are highly advocated. In this context, we investigated an extract of the alpine plant Edelweiss, Leontopodium alpinum var. Helvetia, for its ability to modulate hair follicle (HF) growth ex vivo and inhibit hair loss while increasing hair regeneration in vivo. Methods: Human amputated HFs were microdissected from three donors, two women and one man, and cultured ex vivo for 6 days. After treatment with 0.001% Edelweiss extract (EWDE), we investigated hair shaft production and anagen/catagen conversion, and measured known parameters associated with hair growth, that is hair matrix keratinocyte proliferation and apoptosis, dermal papilla inductivity, and growth factors, by quantitative (immuno)histomorphometry. To assess the anti‐hair loss potential of the alpine plant compound, we performed a randomized, placebo‐controlled human study enrolling Caucasian women and men, aged 18 to 65 years, with normal hair loss. After 5 months' daily use of an extract containing leave‐on serum, we analysed hair density and anagen‐to‐catagen/telogen ratio by the Trichogram analysis. Results: Our results revealed a significant prolongation in the anagen phase in HFs treated with 0.001% Edelweiss, as indicated by an increase in HFs remaining in anagen and a significant decrease in hair cycle score. In line with this effect, EWDE significantly stimulated hair matrix (HM) keratinocyte proliferation, and dermal papilla inductivity, as shown by a significant up‐regulation of versican expression and alkaline phosphatase activity, and a tendential increase in FGF7 immunoreactivity in the dermal papilla of all HFs or only anagen VI HFs. Corroborating the ex vivo results, we observed a significant increase in growing hair shaft numbers (hair density) after treatment with Edelweiss extract formulation, and a tendential up‐regulation in the anagen‐to‐catagen/telogen ratio. Conclusions: We show here, through several lines of evidence, that the selected extract of the alpine plant Leontopodium alpinum var Helvetia (Edelweiss) inhibits premature catagen induction, possibly by stimulating dermal papilla inductivity. It is therefore worth exploiting this extract clinically as an anti‐hair loss agent, both for preventing ageing‐associated hair shedding and as an adjuvant therapy for hair loss disorders. Abstract : An extract of the alpine plant Edelweiss prolongs anagen phase and increases matrix keratinocyte proliferation in human hair follicles. The extract enhances hair density for fuller hair in Caucasian volunteers. Résumé: Objectifs: La perte de cheveux et la réduction du volume des cheveux sont caractéristiques des troubles capillaires, tels que l'effluvium télogène, ou la calvitie chez l'homme ou la femme, et le vieillissement des cheveux, qui peuvent causer une certaine détresse chez les hommes et les femmes. Les médicaments courants contre la chute des cheveux ont des effets secondaires, par conséquent, de nouvelles approches plus sûres ciblant des phénotypes légers sont fortement recommandées. Dans ce contexte, nous avons étudié un extrait de la plante alpine Edelweiss, Leontopodium alpinum var. Helvetia, pour sa capacité à stimuler la croissance du follicule pileux (HF) ex vivo et à inhiber la chute des cheveux tout en augmentant la régénération des fibres capillaires in vivo. Méthodes: Les follicules pileux (HF) humains prélevés ont été microdisséqués chez trois donneurs, deux femmes et un homme, et cultivés ex vivo pendant 6 jours. Après le traitement avec l'extrait d'Edelweiss à 0, 001 % (EWDE), nous avons étudié la production de fibre capillaire et la conversion anagène/catagène, ainsi que mesuré les paramètres connus associés à la croissance des cheveux, à savoir, la prolifération des kératinocytes dans la matrice capillaire et l'apoptose, l'induction des papilles dermiques, et des facteurs de croissance, par (immuno‐)histomorphométrie quantitative. Pour évaluer le potentiel des propriétés anti‐chute du cheveu de l'extrait de plante alpine, nous avons réalisé une étude clinique aléatoire avec placebo, sur des femmes et des hommes de type caucasien âgés de 18 à 65 ans présentant une perte de cheveux normale. Après cinq mois d'utilisation quotidienne d'un sérum sans rinçage contenant l'extrait de plante, nous avons analysé la densité capillaire et le rapport anagène à catagène/télogène par trichogramme. Résultats: Nos résultats ont révélé une prolongation significative de la phase anagène dans les HF traités avec 0, 001% d'Edelweiss, comme l'indique une augmentation des HF restant en phase anagène et une diminution significative du « hair cycle score ». En ligne avec cet effet, EWDE a stimulé de façon significative la matrice du cheveux (HM), la prolifération des kératinocytes, et l'induction de la papille dermique, comme le montre une augmentation significative de l'expression du versican et de l'activité de la phosphatase alcaline, et une augmentation tendancielle de l'immunoréactivité FGF7 dans la papille dermique de tous les HF ou seulement des HF anagènes VI. Corroborant les résultats ex vivo, nous avons observé une augmentation significative du nombre de fibres capillaires (densité de cheveux) après le traitement avec la formulation d'extrait d'Edelweiss, et une augmentation tendancielle dans le rapport anagène à catagène/télogène. Conclusions: Nous montrons ici, à travers plusieurs éléments de preuve, que l'extrait sélectionné de la plante alpine Leontopodium alpinum var Helvetia (Edelweiss) inhibe l'induction prématurée de la phase catagène, en stimulant la papille dermique. Il est donc possible d'utiliser cet extrait comme un agent anti‐chute, à la fois pour prévenir la chute des cheveux associée au vieillissement mais aussi comme une thérapie complémentaire pour les troubles liés à la perte des cheveux.